(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Medical education forms the foundation for competent and compassionate healthcare professionals. Learning Forensic Medicine and Toxicology plays a crucial role in understanding the medico-legal aspects. Teaching comprises all basic, pre-clinical and practical aspects of the subject and provides scientific expertise in investigating deaths, injuries, and poisoning cases. Thus teaching the subject with core concepts understandable to the intended audience is of paramount importance yet has not been explored in this particular subject. Problem-based learning (PBL) is a widely used educational approach in medical education, given the fact the study aims to investigate preferences about different approaches of PBL learning. Subjects and methods: The study was a descriptive cross-sectional out at the Department of Forensic Medicine and Toxicology, Sahara Medical College, Narowal from January to December 2023. The sample size of 100 students was determined using standard educational research practices, considering the course enrollment, expected response rate, and statistical power. This was based on a 95% confidence level, a 5% margin of error, and a population of 513, ensuring precise findings. Results: The students highly valued student-centred learning (93%) and reflection and evaluation (100%). Preferences were mixed for aspects like authentic problems (73% positive, 27% concern), collaborative learning (59% positive, 41% concern), and integration of knowledge and skills (71% positive, 29% concern). Most students (89%) appreciated self-directed learning, with some concerns (11%). Conclusion: The study revealed that students highly valued student-centred learning and reflection in PBL while expressing concerns about authentic problems, collaborative learning and integration of knowledge and skills. Addressing concerns through curriculum refinement can enhance student engagement and skill development in Forensic Medicine. Further research with diverse populations is needed to understand the broader impact of PBL on learning outcomes. The study revealed interventional significance in terms of improvement in academic grades of PBL on learning outcomes.